(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Three specimens of Ammonites have been newly found in the Calcari Grigi Fm. (Lower and Middle Liassic). At present the total amount of known Ammonite specimens in the western part of the Venetian Liassic Carbonate Platform is at least of six. The occurrence of Ammonites ln an unfavourable environment suggests a post—mortem transport from the adjacent Lombardian Basin.